FONEM KONSONAN DAN VOKAL BAHASA BALI DI KABUPATEN TABANAN: KAJIAN DIALEKTOLOGI STRUKTURAL - Subagia I Ketut; Dyah Pertiwi Putri Dewa Ayu (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
This study aims to investigate the phonological variations of the Balinese language in Tabanan Regency and to map them. Observations were made in four villages, namely Bongan, Berembeng, Sanda, and Wangaya Gede. Data were collected by using interview and observation methods.The data are swadesh words spoken by the informants during the interview. The results obtained were that the phoneme /É™/ in the final open position has two realizations, namely [a] and [É™]. Each sound has a different area. [É™] found at the observation point 1,2,4 and [a] found at the observation point 3. The phoneme /e/ at the open end position has two variations, namely [e] and [Îµ], while the phoneme /o/ realized by [o] and [É”]. [e] and [o] were found at the observation point 1,2 4, while [Îµ ] and [É”] were found in TP 3. In addition, there was also difference in the realization of the /k/ consonant phoneme. The phoneme /k/ is realized by [k] and [?]. [k] was used in TP3, while [?] used in TP 1,2,4. In TP 1,2,4 there was not phoneme /a/ in the final distribution, while TP 3 has a complete /a/ distribution. Areas that have a complete phoneme /a/ distribution, [É™] would not be found in the final distribution. In areas where the phoneme /a/ has incomplete distribution, [É™] has a complete distribution there. [k] in the final distribution was unknown at TP3, but known in TP 1,2,4. Meanwhile [?] in the final distribution was known merely in TP 1,2,4 but not in TP 3. Keywords: phoneme; consonant; vowel; Dialectology